Continent urinary diversion using the appendix as a catheterizable stoma - Fujisawa, M (Hinyokika kiyo. Acta urologica Japonica, 1991)
Two patients with bladder cancer underwent construction of continent urinary reservoir using the in situ appendix as a catheterizable stoma after total cystectomy. Urodynamic study revealed that the reservoir had a large capacity of 500-800 ml and low pressure without the involuntary pressure spikes was maintained. X-rays of the reservoir showed no reflux. The patients achieved complete day and night-time continence